High-Entropy Materials: Features for Lithium–Sulfur Battery Applications - Yikun Yao; Jiajun Chen; Rong Niu; Zhenxin Zhao; Xiaomin Wang (Metals, 2023)
The emergence of various electronic devices and equipment such as electric vehicles and drones requires higher energy density energy storage devices. Lithium–sulfur batteries (LSBs) are considered the most promising new-generation energy storage system owing to its high theoretical specific capacity and energy density. However, the severe shuttle behaviors of soluble lithium polysulfides (LiPSs) and the slow redox kinetics lead to low sulfur utilization and poor cycling stability, which seriously hinder the commercial application of LSBs. Therefore, various catalytic materials have been employed to solve these troublesome problems. High entropy materials (HEMs), as advanced materials, can provide unique surface and electronic structures that expose plentiful catalytic active sites, which opens new ideas for the regulation of LiPS redox kinetics. Notwithstanding the many instructive reviews on LSBs, this work aims to offer a complete and shrewd summary of the current progress in HEM-based LSBs, including an in-depth interpretation of the design principles and mechanistic electrocatalysis functions, as well as pragmatic perspectives.